Effects of Pisha sandstone content on solute transport in a sandy soil. (February 2016) - Zhen, Qing; Zheng, Jiyong; He, Honghua; Han, Fengpeng; Zhang, Xingchang
Abstract: In sandy soil, water, nutrients and even pollutants are easily leaching to deeper layers. The objective of this study was to assess the effects of Pisha sandstone on soil solute transport in a sandy soil. The miscible displacement technique was used to obtain breakthrough curves (BTCs) of Br − as an inert non-adsorbed tracer and Na + as an adsorbed tracer. The incorporation of Pisha sandstone into sandy soil was able to prevent the early breakthrough of both tracers by decreasing the saturated hydraulic conductivity compared to the controlled sandy soil column, and the impeding effects increased with Pisha sandstone content. The BTCs of Br − were accurately described by both the convection-dispersion equation (CDE) and the two-region model (T-R), and the T-R model fitted the experimental data slightly better than the CDE. The two-site nonequilibrium model (T-S) accurately fit the Na + transport data. Pisha sandstone impeded the breakthrough of Na + not only by decreasing the saturated hydraulic conductivity but also by increasing the adsorption capacity of the soil. The measured CEC values of Pisha sandstone were up to 11 times larger than those of the sandy soil. The retardation factors (R) determined by the T-S model increased with increasing Pisha sandstone content, and the partition coefficient (Kd ) showed a similar trend to R. According to the results of this study, Pisha sandstone can successfully impede solute transport in a sandy soil column. Highlights: Pisha sandstone can successfully impede solute transport in a sandy soil column. Pisha sandstone impeded the breakthrough of Br − and Na + by decreasing the saturated hydraulic conductivity. Pisha sandstone impeded the breakthrough of Na + also by increasing the adsorption capacity of the soil.